1996
DOI: 10.1007/bf02684180
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and finite-element model investigation of the conductance technique for measurement of aortic segmental volume

Abstract: This investigation examined the feasibility of applying the conductance catheter technique for measurement of absolute aortic segmental volume. Aortic segment volume was estimated simultaneously in vitro by using the conductance catheter technique and sonomicrometer crystals. Experiments were performed in five isolated canine aortas. Vessel diameter and pressure were altered, as were the conductive properties of the surrounding medium. In addition, a three-dimensional finite-element model of the vessel and app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 15 publications
2
17
0
Order By: Relevance
“…The blood vessel length downstream of stenosis was shown to be sufficient for the largest recirculation bubble observed in the flow conditions studied. The computa-tional domain in the radial direction including blood vessel lumen and surrounding tissue is similar to previous conductance catheter studies (9,15). Governing equations and numerical methods.…”
Section: Methodsmentioning
confidence: 94%
“…The blood vessel length downstream of stenosis was shown to be sufficient for the largest recirculation bubble observed in the flow conditions studied. The computa-tional domain in the radial direction including blood vessel lumen and surrounding tissue is similar to previous conductance catheter studies (9,15). Governing equations and numerical methods.…”
Section: Methodsmentioning
confidence: 94%
“…It is agreed that the nonhomogeneity of the electric field is much less of a problem when applying the conductance technique in the aorta than in the left ventricle because the vessel more closely adheres to the cylindrical model (11). In blood vessels, Hettrick et al (12) showed that the value of ␣ is near unity for small cylinders (Ͻ10 mm in diameter) in a finite-element simulation and in in vitro measurements.…”
Section: Discussionmentioning
confidence: 99%
“…THE CONDUCTANCE CATHETER METHOD, which has been used previously to measure ventricular volume (4 -5, 7, 14 -16, 29, 30, 33), has recently been adapted to determine the crosssectional area (CSA) of the aorta (11)(12)(13). The conductance catheter technique is based on a cylindrical model by measuring the electrical impedance of the blood with two outer electrodes for excitation and two inner electrodes for detection to yield the CSA of the chamber of interest.…”
mentioning
confidence: 99%
“…The length of blood vessel segment (30 mm) was set to be sufficient to encompass the electric field by four electrodes of conductance catheter (0.9 mm diameter corresponding to 0.035 00 ). The computational domain in the radial direction, including blood vessel lumen and surrounding tissue, is more anatomically relevant, while the domain was assumed to be cylindrically axisymmetric in the previous conductance catheter studies [7,9,12].…”
Section: Geometry and Computational Domainmentioning
confidence: 99%
“…The conductance catheter has been widely adopted for sizing the chamber volume of ventricles [1 -5] and the luminal diameter of aorta [6,7] and medium-size arteries [8 -11]. Two bolus injections of saline solutions with known electrical conductivities (e.g.…”
Section: Introductionmentioning
confidence: 99%